2020
DOI: 10.5194/essd-12-2061-2020
|View full text |Cite
|
Sign up to set email alerts
|

Isoscape of amount-weighted annual mean precipitation tritium (<sup>3</sup>H) activity from 1976 to 2017 for the Adriatic–Pannonian region – AP<sup>3</sup>H_v1 database

Abstract: Abstract. Tritium (3H) as a constituent of the water molecule is an important natural tracer in hydrological sciences. The anthropogenic tritium introduced into the atmosphere unintentionally became an excellent tracer of processes on a time scale of up to 100 years. A prerequisite for tritium applications is to know the distribution of tritium activity in precipitation. Here we present a database of isoscapes derived from 41 stations for amount-weighted annual mean tritium activity in precipitation for the pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Recent studies suggest that the solar cycles 10–12 years impart ca. ± 20% of fluctuation in Central Europe that gets overprinted on annual 3 H seasonality 17 , 18 . In our analysis we found that 3 H records with at least three years of continuous monthly sampling, whether during the rising or falling limb of the solar cycle, corresponded within the 3 H measurement uncertainty to the stations’ mean value for the period 2008–2018.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that the solar cycles 10–12 years impart ca. ± 20% of fluctuation in Central Europe that gets overprinted on annual 3 H seasonality 17 , 18 . In our analysis we found that 3 H records with at least three years of continuous monthly sampling, whether during the rising or falling limb of the solar cycle, corresponded within the 3 H measurement uncertainty to the stations’ mean value for the period 2008–2018.…”
Section: Methodsmentioning
confidence: 99%
“…We examined contemporary global distribution patterns of 3 H in Earth’s precipitation within the “post-bomb” hydrologic timeframe 11 , in the absence of new anthropogenic 3 H alterations having global impacts other than natural solar flux cycles 17 19 and constraining our analysis to the years 2008–18 for data availability reasons. We focused our efforts on monthly precipitation composites and 3 H data from the IAEA GNIP database 20 and published data (see discussion in Supplementary Material S M1 ), with the aim to produce high spatial resolution predictive maps of annual 3 H in Earth’s rainfall.…”
Section: H In Global Precipitationmentioning
confidence: 99%
“…Nonetheless, more robust interpretations of the above uses for 3 H distributions could be made with regular monitoring of well distributed samples locations, as were in California by Visser et al (2016). A similar approach was undertaken in Kern et al (2020), where temporal records of precipitation from multiple stations in the Adriatic-Pannonian region were used to build isoscapes of 3 H in precipitation by using data collected by the IAEA GNIP program. However, the monitoring of environmental 3 H at such a resolution that isoscapes can be compared over time would require an improvement in local analytical capabilities in southern Africa.…”
Section: Current and Future Context Of 3 H Distributionsmentioning
confidence: 99%
“…Catchment scale investigations show that tritium-based assessments of modern recharge and residence time are more nuanced than a global evaluation can capture (Gusyev et al, 2016). It is also evident that the variation of background 3 H in local rainfall is more significant than reported in older studies (Kern et al, 2020;van Rooyen, Palcsu, et al, 2020a;Visser et al, 2018). Once 3 H reaches the subsurface through recharge, its abundance is predominantly dependent on decay as the subsurface production of 3 H is limited to areas nearby radioactive landfills or waste sites (Hughes et al, 2011).…”
mentioning
confidence: 93%
“…where γ(h) is the semivariogram and Z(x) and Z(x + h) are the values of a parameter sampled at a planar distance |h| from each other, N(h) is the number of lag-h differences, i.e., n × (n − 1)/2 and n corresponds to the number of sampling locations at a distance h. The most important properties of the semivariogram used in the present study are the nugget, which quantifies the variance at the sampling location (including information regarding the error of the sampling), the sill, that is, the level at which the variogram stabilizes, which is the sum of the nugget (c 0 ) and the reduced sill (c), and the range (a), which is the distance within which the samples have an influence on each other and beyond which they are uncorrelated [68,69]. If the semivariogram does not have a rising part and the points of the empirical semivariogram align parallel to the abscissa, a nugget-type variogram is obtained.…”
Section: Variography and Interpolationmentioning
confidence: 99%